Agrarian Reform and Land Redistribution in Palu City: Addressing Post-Disaster Challenges - Jusuf Ano; Daswati Daswati; Sitti Chaeriah Ahsan; Syahruddin Hattab; Mustainah Mustainah (Faculty of Law, Universitas Pekalongan, 2023)
This study investigates the implementation of agrarian reform policy in Palu City, Central Sulawesi Province. Adopting a qualitative research design, the study involved purposive sampling of five key informants. Data were collected through a combination of observation, in-depth interviews, and documentation, and analyzed descriptively. The findings, analyzed through the lens of Merilee S. Grindle's theory, identify two critical factors: the content of the policy and the context of its implementation. Regarding policy content: (1) The interests of both the implementers and the target groups—primarily the local community—were found to remain largely unaffected, socially and economically, as evidenced by the absence of opposition to the agrarian reform policy; (2) The benefits associated with the policy, particularly in enhancing community welfare through the establishment of agrarian reform villages, were perceived as significant; (3) The anticipated changes, such as the acquisition of new knowledge and skills by the community, were achieved; (4) The role of policymakers has been effectively institutionalized, as demonstrated by the Mayor’s Decree on the Agrarian Reform Task Force (GTRA), which has successfully engaged relevant stakeholders; (5) Despite encountering some challenges, the implementation of the agrarian reform policy has progressed effectively; (6) The resources allocated, particularly those from the Palu City Land Office, have been utilized optimally. In terms of the implementation context: (1) The power dynamics, interests, and strategies of the involved actors have been pivotal in driving the successful realization of the policy’s objectives; (2) The characteristics of the institutions and authorities involved have provided robust support for the policy’s implementation in Palu City; (3) Compliance and responsiveness within the implementation framework have been optimized, reflecting a strong commitment and support from the Palu City Government. The study concludes that the implementation of agrarian reform policy in Palu City has been effective and well-coordinated.